2012
DOI: 10.1017/s0033291712000451
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between executive functions and fluid intelligence in Parkinson's disease

Abstract: BackgroundWe recently demonstrated that decline in fluid intelligence is a substantial contributor to frontal deficits. For some classical ‘executive’ tasks, such as the Wisconsin Card Sorting Test (WCST) and Verbal Fluency, frontal deficits were entirely explained by fluid intelligence. However, on a second set of frontal tasks, deficits remained even after statistically controlling for this factor. These tasks included tests of theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
31
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 52 publications
9
31
2
1
Order By: Relevance
“…Correlation analyses revealed that FI was linked to cognitive flexibility and processing speed only for children with AS. Our data are consistent with recent studies suggesting that FI is a substantial contributor to classical EF tasks (such as TMT) in neurological patients (Roca et al, 2010, 2012). However, this effect cannot be attributed to a positive correlation between FI and all frontal functions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Correlation analyses revealed that FI was linked to cognitive flexibility and processing speed only for children with AS. Our data are consistent with recent studies suggesting that FI is a substantial contributor to classical EF tasks (such as TMT) in neurological patients (Roca et al, 2010, 2012). However, this effect cannot be attributed to a positive correlation between FI and all frontal functions.…”
Section: Discussionsupporting
confidence: 93%
“…However, this effect cannot be attributed to a positive correlation between FI and all frontal functions. In the present study, ToM was not correlated with FI, as reported elsewhere in the literature (Roca et al, 2010, 2012). …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some evidence supports a stronger association between executive functions and “fluid intelligence,” both involving mainly dorsolateral prefrontal networks (Roca et al, 2012), in contrast to ToM processes, hypothesized to be probably more dependent from medial prefrontal networks, especially with regard to the affective subcomponent (Shamay-Tsoory et al, 2005, 2006; Xi et al, 2011; Bertoux et al, 2016). However, more recently, Burke et al (2016b) demonstrated a significant impairment of ET, as a measure of affective social cognition, in ALS patients with executive dysfunctions compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, multiple studies have shown that fluid intelligence deficits are responsible for the deficits observed in classical executive tests in different neurological and psychiatric conditions. Data from different clinical groups, including patients with frontal lobe lesions (Roca et al, 2010), Parkinson's disease (Roca et al, 2012), Frontotemporal Dementia (Roca et al, 2013), and Schizophrenia (Roca et al, 2014), have consistently shown that after factoring out the effects of g , no differences between patients and controls remain for classical executive tests, such as the Wisconsin Card Sorting Test (WCST), Verbal Fluency, and Trail Making Test B (TMTB). On the contrary, other frontal tests, including tests of multitasking and of social cognition, are not explained by differences in g. This discordance has been attributed to the fact that those multitasking and social cognition tasks reflect anterior prefrontal deficits rather than the dorsolateral deficits associated with g and classical executive deficits (Roca et al, 2010).…”
Section: Introductionmentioning
confidence: 99%